Molecular cloning, tissue distribution and nutritional regulation of four acyl-coenzyme A oxidase (acox) isoforms in Scylla paramamosain - Lin Zhideng; Lan Jinjie; Lin Huangbin; Huang Chaoyang; Zhang Mingyao; Huang Qincheng (Frontiers in Marine Science, 2024)
As rate-limiting enzymes of peroxisomal β-oxidation, acyl-coenzyme A oxidase (ACOXs) play vital roles in maintaining energy homeostasis and regulating reactive oxygen species (ROS) metabolism. However, there are no studies on the functions of ACOXs in crustaceans. In the present study, four full-length cDNA sequences of acoxs , namely the acox-1a (2403 bp), acox-1b (2733 bp), acox-3a (2878 bp) and acox-3b (3445 bp), were successfully isolated from mud crab Scylla paramamosain , which encoded 666, 673, 701 and 658 amino acids, respectively. Sequence analysis showed that the ACOX-1a, ACOX-1b and ACOX-3a possessed conserved structural domains like FAD-binding motif, fatty acyl CoA oxidase domain and peroxisomal targeting signal, while the ACOX-3b lacked peroxisomal targeting signal. Results of phylogenetic tree indicated that the four ACOXs of mud crab grouped gathered with their corresponding orthologues from crustaceans. The acox-1a , acox-3a and acox-3b were highly expressed in hepatopancreas, and the acox-1b was mainly distributed in muscle and hepatopancreas. Compared with feeding groups, the expression levels of acox-1a , acox-3a and acox-3b in hepatopancreas and acox-3a in muscle were markedly up-regulated in fasting groups, suggesting that the acoxs had significant effects in modulating energy balance during fasting. In addition, fasting significantly increased the transcriptional levels of nuclear factor erythroid 2-related factor ( nrf2 ) and its downstream antioxidant genes (catalase ( cat ), glutathione peroxidase ( gpx ) and glutathione S-transferase ( gst )) to improve antioxidant capacity for removing excessive ROS produced by ACOX-mediated peroxisomal β-oxidation. These results would be conducive to providing new insights into evolutionary characteristics and functions of acoxs in crustaceans.

High expression of NEK2 promotes gastric cancer progression via activating AKT signaling - Hao Wan; Lin Xu; Huangbin Zhang; Feixiang Wu; Weiqiang Zeng; Taiyuan Li (Journal of Physiology and Biochemistry, 2021)